The DIAMOND trial – DIfferent Approaches to MOderate & late preterm Nutrition: Determinants of feed tolerance, body composition and development: protocol of a randomised trial - Laura Galante (BMC Pediatrics, 2018)
Background: Babies born at moderate-late preterm gestations account for > 80% of all preterm births. Although survival is excellent, these babies are at increased risk of adverse neurodevelopmental outcomes. They also are at increased risk of adverse long-term health outcomes, such as cardiovascular disease, obesity and diabetes. There is little evidence guiding optimal nutritional practices in these babies; practice, therefore, varies widely. This factorial design clinical trial will address the role of parenteral nutrition, milk supplementation and exposure of the preterm infant to taste and smell with each feed on time to tolerance of full feeds, adiposity, and neurodevelopment at 2 years. Methods/design: The DIAMOND trial is a multi-centre, factorial, randomised, controlled clinical trial. A total of 528 babies born between 32+ 0 and 35+ 6 weeks’ gestation receiving intravenous fluids and whose mothers intend to breastfeed will be randomised to one of eight treatment conditions that include a combination of each of the three interventions: (i) intravenous amino acid solution vs. intravenous dextrose solution until full milk feeds established; (ii) milk supplement vs. exclusive breastmilk, and (iii) taste/smell given or not given before gastric tube feeds. Babies will be excluded if a particular mode of nutrition is clinically indicated or there is a congenital abnormality. Primary study outcome: For parenteral nutrition and milk supplement interventions, body composition at 4 months’ corrected age. For taste/smell intervention, time to full enteral feeds defined as 150 ml.kg− 1.day− 1 or exclusive breastfeeding. Secondary outcomes: Days to full sucking feeds; days in hospital; body composition at discharge; growth to 2 years’ corrected age; development at 2 years’ corrected age; breastfeeding rates. Discussion: This trial will provide the first direct evidence to inform feeding practices in moderate- to late-preterm infants that will optimise their growth, metabolic and developmental outcomes.